2005
DOI: 10.1242/jcs.01694
|View full text |Cite
|
Sign up to set email alerts
|

The chemokine SDF-1 differentially regulates axonal elongation and branching in hippocampal neurons

Abstract: Recent data have shown that the chemokine SDF-1 plays a critical role in several aspects of brain development such as cell migration and axon pathfinding. However, its potential function in the generation of axons and dendrites is poorly characterized. In order to better understand the role of SDF-1 in the development of central neurons, we studied the cellular distribution of the SDF-1 receptor CXCR4 by immunocytochemistry of developing hippocampal neurons and tested the effect of SDF-1 in process patterning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 50 publications
4
88
0
Order By: Relevance
“…A previous study showed that the cellular localization of CXCR4 changes during the maturation of rat hippocampal neurons (Pujol et al 2005). In this study, neuronal precursors differentiated in NB27 showed a broad expression of CXCR4 on both the cell body and neurites (Fig.…”
Section: Cellular Localization Of Cxcr4 Changes As Neurons Maturatesupporting
confidence: 60%
“…A previous study showed that the cellular localization of CXCR4 changes during the maturation of rat hippocampal neurons (Pujol et al 2005). In this study, neuronal precursors differentiated in NB27 showed a broad expression of CXCR4 on both the cell body and neurites (Fig.…”
Section: Cellular Localization Of Cxcr4 Changes As Neurons Maturatesupporting
confidence: 60%
“…[61][62][63] Potentially, such podocyte precursors of glomerular parietal epithelial cell origin may be involved in the repopulation of the glomerular tuft during podocyte injury. 58 -60,64 CXCR4/CXCL12 guide cell migration in a number of systems (eg, renal morphogenesis (tubulogenesis), neuron/ axon development, and tumor metastasis [65][66][67][68] ). Using an in vitro wound healing assay to evaluate CXCR4-dependent migration, we could demonstrate that treatment of cultured podocytes with a blocking CXCR4 antibody significantly impaired in vitro wound healing and hence CXCR4-dependent cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Rat hippocampal and cortical cultures were prepared from 18-d-old rat embryos by previously described methods (Goslin et al, 1998;Pujol et al, 2005). Briefly, hippocampi were dissected and dissociated by trypsin and trituration and plated on glass coverslips coated with poly-l-lysine.…”
Section: Cell Culturesmentioning
confidence: 99%